[INVITED] Evaluation of process observation features for laser metal welding. (June 2016) - Tenner, Felix; Klämpfl, Florian; Nagulin, Konstantin Yu.; Schmidt, Michael
Abstract: In the present study we show how fast the fluid dynamics change when changing the laser power for different feed rates during laser metal welding. By the use of two high-speed cameras and a data acquisition system we conclude how fast we have to image the process to measure the fluid dynamics with a very high certainty. Our experiments show that not all process features which can be measured during laser welding do represent the process behavior similarly well. Despite the good visibility of the vapor plume the monitoring of its movement is less suitable as an input signal for a closed-loop control. The features measured inside the keyhole show a good correlation with changes of process parameters. Due to its low noise, the area of the keyhole opening is well suited as an input signal for a closed-loop control of the process. Abstract : Highlights: We analyzed the laser welding process with two high-speed cameras. We measured the dynamic of process features for different process parameters. We measured the delay between changes of process parameters and features. We found that the keyhole opening is well correlated to different process parameters. We found that the vapor plume evolution is delayed to the parameter changes.